The Strategic Advantage of Impulsivity in Entrepreneurial Action: An Agent-Based Modeling Approach - Bort, James; Wiklund, Johan; Crawford, Christopher; Lerner, Daniel; Hunt, Richard (Sage Journals, 2023)
Our study extends and enhances entrepreneurial action theory (EAT) by considering the strategic advantage or disadvantage of impulsive action. To date, EAT has largely sidestepped the role of dispositional impulsivity, limiting its veridicality and inclusivity. Popularized notions of celebrity entrepreneurs and an increasingly large body of empirical research on the prevalence of impulsivity have inspired a reassessment of what drives entrepreneurs. Looking beyond both the anecdotes and well-established prevalence of impulsivity, we develop and illustrate a novel theory concerning the fate of impulsive nascent entrepreneurs who are wired for nondeliberative, less-calculative action. We use an agent-based model and conduct simulation-based experiments involving 2.7 million virtual entrepreneurs to identify and explicate the specific conditions under which impulsivity does or does not generate strategic advantage. Accordingly, we contribute a broader and deeper theorization of EAT, taking notable steps toward the inclusion of nontraditional entrepreneurs and the varied impacts of impulsive action in this domain’s evolving conception of new venture emergence.
Keywords: Experimental methods/simulation; Research methods; Specialty areas; Start-up; New ventures; Psychology; General areas; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 1 - Fin de la pobreza; ODS 5 - Igualdad de género; ODS 9 - Industria, innovación e infraestructura; ODS 10 - Reducción de las desigualdades